Evaluation of the impact of mulch on crop productivity in Florida 91 tomato and pepper varieties - Dray, Mariah (My University, 2025)
In northeastern Kansas, USA, agricultural practices are challenged by environmental factors, which can impact crop yields and farming sustainability. Primary factors for stress in crop growth include drought, extreme temperatures, frost and freeze events, flooding, wind stress, pests and diseases, soil degradation and erosion. Agricultural practices in northern Kansas are subject to environmental, physical, or biological stress. Crop growers must negotiate these issues when implementing conservation methods (e.g., water conservation and retention, crop rotation, resilient varieties) to aid in crop production. Understanding the stress experienced by plants, organisms, or their system is important for addressing challenges and successfully adapting solutions through thoughtful planning, flexibility, and innovation. I investigated the total weight and total number of fruit of two crop types: Florida 91 tomatoes and two varieties of sweet peppers, California Wonder and Outsider. My objective was to compare crop performance in terms of total weight per plant and total number of fruits under outdoor environmental growing conditions. My experimental approach utilized a randomized complete block design with four replications for each variety. I tested Florida 91 tomato yield production under three mulch varieties of hemp hurd, straw, and plastic material compared to a bare soil plot. The pepper study compared two sweet pepper varieties grown under hemp hurd. I collected data over an 18-week study in the 2023 growing season and evaluated individual plants for total weight and total number per soil cover at weekly interval harvest. There was no significant difference in weight between tomato treatments and in all pepper varieties. Nonetheless, Florida 91 tomatoes are more suited for high-yield production, and sweet peppers excelled, under mulched soil coverage. I found the soil cover positively affected tomato weight and production consistency throughout the growth season. My results can provide valuable insights into agricultural practices aimed at optimizing yield and crop management for both tomatoes and sweet peppers through sustainable conservation methods.
Keywords: Soil cover; Mulch; Tomato; Sweet pepper